Constructing HIV and Magic Johnson: Discourse, education and power - Roger Boshier (Adult Education Research Conference, 1993)
The author analyzed the construction f Magic Johnson in the mainstream media, the gay press, the superpulp press and the black press. Five tropes emerged - heroic figure discourse, homophobia discourse, heterosexual titillation discourse, athletic promscuity discourse, fallen hero discourse. Implications for education are described.